Solution of RE Models with Anticipated Shocks and Optimal Policy - Hans-Werner Wohltmann; Roland C. Winkler (Kiel University, Department of Economics, 2007)
The purpose of this paper is to solve linear dynamic rational expectations models with anticipated shocks by using the generalized Schur decomposition method. We also determine the optimal unrestricted and restricted policy responses to temporary as well as permanent shocks which both are anticipated by the public. In particular, our method is useful for the analysis of optimal monetary policy in New Keynesian dynamic general equilibrium models.
Keywords: E52; C61; C32; 330; Anticipated Shocks; Optimal Monetary Policy; Rational Expectations; Generalized Schur Decomposition; Ungleichgewichtstheorie; Dynamisches Gleichgewicht; Allgemeines Gleichgewicht; Schock; Rationale Erwartung; Dekompositionsverfahren; Dekompositionsverfahren; Geldpolitik; Theorie